Cross-country spillovers of renewable energy promotion: The case of Germany - Jan Abrell; Mirjam Kosch (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
Electricity generation based on renewable energy (RE) sources such as wind and solar replace the most expensive generators that often rely on fossil fuels. In response to RE promotion, wholesale electricity prices and carbon emissions are therefore expected to decrease. In interconnected electricity systems, this so-called merit- order effect stimulates a change in electricity trade ows. Therefore, conventional generation and prices in neighboring countries are also likely to decrease. The impact of these trade reactions on carbon offsets is ambiguous and depends on installed generation and interconnector capacities. Moreover, the cross-border merit-order effect causes opposing effects on consumers and producers: Generators' profits decline, while consumers benefit from lower electricity costs and an increase in the consumer surplus. Using a rich data set of hourly technology-specific generation and wholesale market price data for ten central European countries, we estimate the domestic and cross-border impacts of German RE for the years 2015 to 2020. We find that German RE generation offset 79 to 113 MtCO2 per year. The major emission effect took place in Germany (64 - 99 MtCO2). The average cost of emission offset of 212 to 321e/t were almost entirely borne by German market participants. Neighboring countries do not bear costs, but a significant shift from producer to consumer rents is observed.
Keywords: Q41; Q42; Q58; 330; Renewable promotion; Electricity prices; Merit-order effect; Cross-border impacts; Carbon emissions